Design, Synthesis, Antiviral and Cytotoxicity Studies of Some 2-Phenyl-3-substituted quinazolin-4-(3H)-ones - Saravanan, Sakthi; Selvam, Periyasamy; Ram Lakra, Dhani; De. Clercq, E. (Asian Journal of Chemistry, 2010)
A series of novel 2-phenyl-3-substituted quinazolin-4-(3H)-one derivatives were synthesized and screened for antiviral activity against panel of human pathogenic viruses. The structures of the synthesized compounds were characterized by means of their IR, 1H NMR data. The anti HIV activities of the new compounds were screened in vitro antiviral activity against replication of HIV-1 (IIIB) and HIV-2 (ROD) in MT-4 cells using AZT-as standard. All the compounds displayed cytostatic properties in T-lymphocytes MT-4 cells. The compound 4-[(4-oxo-2- phenylquinazolin-3(4H)-yl-amino]methyl amino benzoic acid (QPAB) (CC50 = 11.90 μg/mL) was found to be more toxic in this series. 2-Amino-3-phenylquinazolin-4(3H)-one (BN) exhibited antiviral activity against Herpes Simplex virus-1,2 and vaccinia virus in HEL cells at the concentration of 10 and 12 μg/mL, whereas cytotoxicity was found to be 100 μg/mL (SI = 10). Among these compounds, compounds (QIS and QMB) exhibited antiviral activity against vesicular stomatitis virus in HeLa cells at the concentration of 12 μg/mL, whereas cytotoxicity was found to be 100 μg/mL (SI = 9).